Renal angiomyolipoma with tuberous sclerosis complex: How it differs from sporadic angiomyolipoma in both management and care - Takashi Hatano; Shin Egawa (Asian Journal of Surgery, 2020)
Renal angiomyolipoma (AML) is the most common benign tumor of the kidney. It consists of blood vessels, smooth muscle and fat components in varying proportions. AML is divided into the sporadic type and tuberous sclerosis complex (TSC)-associated type. TSC-associated AML develops at a younger age and tends to exhibit a much faster growth rate over time than sporadic AML. AMLs are classified as classic AML, fat-poor AML and epithelioid AML. Epithelioid AML, though rare, shows aggressive behavior leading to distant metastasis and mortality. TSC-associated AML is more likely to have an epithelioid component than sporadic AML. Active surveillance is the suggested management for small AML. Clinical intervention is mainly indicated when there is a substantial risk of rupture. Minimally invasive therapies, including partial nephrectomy, transcatheter arterial embolization, and mammalian target of rapamycin (mTOR) inhibitor treatment are employed for patients who require treatment. An updated algorithm for the management of AML is herein described. According to this algorithm, treatment intervention is recommended for TSC-associated AML >3 cm, even in asymptomatic cases. In cases with asymptomatic sporadic AML >4 cm in size or with an intra-tumoral aneurysm of >5 mm, treatment, including transcatheter arterial embolization or partial nephrectomy, is advised. The major complication of AML is intra-tumoral or retroperitoneal hemorrhage due to rupture that may be serious and life threatening. Thus, correct diagnosis, proper observation, and appropriate treatment are very important in the management of renal AML.